Slow takeoff [airport security].
Before 9/11, air travel in the United States was plagued by delays. It still is. But now the stepped-up security in the aftermath of the hijackings has added congestion in terminals to the delays on the tarmac. Since the newly created Transportation Security Administration (TSA) took over US aviation security, US airports have had to be evacuated on more than 100 occasions and hundreds of flights have been recalled to terminals so that passengers could be rechecked. Equipment is a major concern. Explosives detection systems (EDS) are required to screen checked baggage, but aviation officials doubt they can be built and installed in time to meet the legislated 31 December 2002 deadline. Introducing the smaller, less expensive trace-explosive detectors would still require significant numbers of as-yet unbuilt and uninstalled machines. And operators trained to run all of these machines are in exceedingly short supply. To top it off, machines and personnel must somehow be paid for.
Keywords: Transportation Security Administration; United States; Airport security; Aviation officials; Checked baggage screening; Explosives detection systems; Trace-explosive detectors